Comparison of Formula-Based Methods with Diverse TGL: VLDL-C Ratio for Calculating LDL-C in a Tertiary Care Hospital - Chowdary, Maneni V. P. (Journal of Laboratory Physicians, 2021)
Background The most popular Friedewald formula (FF) was tailored with a fixed factor of 5 for triglyceride-very low-density lipoprotein cholesterol (TGL:VLDL-C) ratio. Some of the subsequent studies on diverse population demonstrated modified FF with only altered TGL:VLDL-C ratio, comprising either a fixed or an adjustable factor. Hata and Nakajima as well as Puavilai et al proposed fixed factors of 4 and 6, respectively. Recently, Martin et al recommended an adjustable factor derived as N-strata-specific median TGL:VLDL-C ratio based on TGL and non-high-density lipoprotein cholesterol (non-HDL-C).Aim This comparative retrospective study evaluates the efficacy of LDL-C formulae, varying only in TGL-VLDL-C ratio, using direct LDL-C assay as a reference method in a tertiary care hospital.Materials and Methods A total of 1,747 patient records with lipid profile data were procured. Concordance analysis, absolute difference, and post hoc test were employed as analytical tools. The impact of total cholesterol (TChol), TGL, and HDL-C on formulae was also evaluated.Results Overall, Martin equation had relatively the highest concordance, narrowest absolute difference, and minimal influence of TChol, TGL, and HDL-C. On the contrary, the Hata method revealed comparatively the lowest concordance, widest absolute difference, and high influence of TChol, TGL, and HDL-C. The remaining formula-based approaches, that is, FF and Puavilai calculation, executed mostly inconsistent intermittent features between Martin equation and Hata method.Conclusion Relatively dominant and competitive analytical attributes of the Martin equation with an adjustable TGL:VLDL-C factor outweigh the remaining three formulae-based methods with fixed TGL:VLDL-C factor in Indian adults.
Keywords: total cholesterol; triglycerides; low-density lipoprotein cholesterol; high-density lipoproteins cholesterol; Very low-density lipoprotein cholesterol